Faktor-Faktor Yang Mempengaruhi Kemiskinan Di 10 Provinsi Termiskin Di Indonesia - Anitasari, Merri (Brida Provinsi Jambi, 2025)
This study aims to determine and explain the effect of the Human Development Index, Economic Growth, Per Capita Income, Education Level, Open Unemployment Rate, Inflation and Government Expenditure on the Poverty Rate in 10 Provinces with the highest poverty rate. The analytical method used is descriptive quantitative analysis with a panel data regression model using the Fixed Effect Model from secondary data starting from 2013 - 2023 in 10 provinces there is Papua, West Papua, East Nusa Tenggara, Maluku, Gorontalo, Aceh, Bengkulu, West Nusa Tenggara, Central Sulawesi, and South Sumatra with the highest poverty rate sourced from the Central Statistics Agency (BPS) and the Directorate General of Fiscal Balance (DJPK). The results showed simultaneously that two of the seven independent variables there is education level and open unemployment rate affect the Poverty Rate in the 10 Provinces with the highest poverty rate in 2013-2023. Keywords : HDI, Economic Growth, Per Capita Income, Education Level, Unemployment, Inflation, Government Spending, Poverty Rate.